Gear Up: designing an ESP course for mechanical engineering students - Elizondo González, Jose Fabián (2020)
This article presents the design of the course Gear Up, an ESP course addressed to Mechanical Engineering students at the University of Costa Rica. To gather the necessary data, a needs analysis and a diagnostic test were conducted to determine the contents, macro-skills, and evaluated activities to be included in the course. This article presents the findings of these two major initial activities and the subsequent course design proposal to satisfy the needs, wants, and lacks of both the students and stakeholders that participated in the process. Consequently, Gear Up was created as a 16-week course in which the Task-Based Language Teaching approach would guide both the content and performance-based, assessed activities throughout the course.